2020
DOI: 10.1111/risa.13584
|View full text |Cite
|
Sign up to set email alerts
|

Kitchen Hygiene in the Spotlight: How Cooking Shows Influence Viewers’ Hygiene Practices

Abstract: Poor hygiene when handling food is a major cause of foodborne illness. To investigate whether hygiene practices visible in television cooking shows influence viewers’ kitchen hygiene, a study on the adoption of demonstrated hygiene behavior was conducted under controlled, experimental conditions. In a study ostensibly on cooking by following recipes participants (n = 65) were randomly assigned to one of three conditions, in which they watched a cooking video that differed only with regard to the hygiene behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Consequently, it may require additional steps to highlight the personal relevance of food safety communications, for instance by focusing on specific practices or situational contexts (Jackson & Meah, 2018). In addition, relevant information and safe food‐handling practices could be integrated into formats that convey knowledge in a more indirect way such as TV cooking shows (Koch et al., 2021). However, additional research is needed to confirm that indirect educational formats can help changing long‐established practices in older adults permanently.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it may require additional steps to highlight the personal relevance of food safety communications, for instance by focusing on specific practices or situational contexts (Jackson & Meah, 2018). In addition, relevant information and safe food‐handling practices could be integrated into formats that convey knowledge in a more indirect way such as TV cooking shows (Koch et al., 2021). However, additional research is needed to confirm that indirect educational formats can help changing long‐established practices in older adults permanently.…”
Section: Discussionmentioning
confidence: 99%
“…Sensible domestic hygiene principles seem partly lost. We learn about correct and incorrect hygiene in the kitchen effectively from watching cooking shows [44]. When asked, people generally are not aware to prepare their salad and vegetables before that of their meat, are not conscious of knife hygiene, hand washing, or refrigerator cleanliness (authors' outcomes of inquiries, unpublished).…”
Section: Failing Containment Of Pathogenic Micro-organismsmentioning
confidence: 99%
“…Previous studies have examined the effects of television media and cooking shows on the consumers who watch them from various aspects (Koch et al, 2021; Maughan et al, 2017) and showed that consumers' food handling practices are significantly influenced by the behaviors shown on television cooking shows (Woods & Bruhn, 2016). Woods and Bruhn (2016) reported that about two‐thirds of study participants (self‐report) would mimic correct food safety, and about half would mimic poor hygiene practices demonstrated by a chef.…”
Section: Introductionmentioning
confidence: 99%